A qualitative research of humanitarian workers’ perceptions of preventing Gender-Based Violence (GBV) in the Cox’s Bazar refugee camps, Bangladesh (2019)
During humanitarian crises, there are priorities to solve immediately such as shelter, food and water. Overcrowding in make-shift settlements and rapid population movement in spontaneous settlements and refugee camps, challenge the capacity of humanitarian workers to implement initiatives to prevent GBV. Forms of GBV can be grouped into four general categories such as sexual abuse, physical abuse, emotional and psychosocial abuse and economic abuse. GBV inflicts harm on women and girls. However, how and when GBV interventions take place? When, will, can those issues become a priority? The main objective of this research is to investigate the experiences of GBV interventions in the Cox’s Bazar refugee camps, and how they are perceived by humanitarian workers from different sectors. This is a qualitative interview study, guided by a conceptual framework developed from a literature review on GBV in emergency settings, and the IASC guidelines for integrating GBV interventions in humanitarian action. The data was summarized in a data matrix based on the conceptual framework, and also including emerging issues.